Paleozoogeography of the Wine Mouse (Akodon oenos) & Late Holocene Paleoenvironments in South-Central Mendoza, Argentina - Fernández, Fernando Julián (Ethnobiology Letters, 2011)
Cranial remains of the wine mouse (Akodon oenos) are documented from an archaeological site in south-central Mendoza, Argentina (Agua de La Mula, 35º22’ S, 68º15’ W), which dates to the end of the late Holocene (1610 ± 60; 1260 ± 60; 1000 ± 50 C14 yr B.P.). The taxonomic status of this small rodent is currently being assessed, but these remains represent the first fossil record for the morphotaxon A. oenos. The species’ present distribution is restricted to a few records from Mendoza province. Analysis of the remains supports paleoenvironmental reconstruction using the small mammal assemblage recovered from this site. From the late Holocene into modernity temperature decreased and winter precipitation increased, resulting in advance of Patagonian steppe grading with altitude into Monte desert. Holocene climatic conditions may explain the relatively late human occupation of ecologically marginal environments in this region, which probably favored effective human occupation of the Payunia region at sites such as Agua de La Mula between 1600 and 1000 years B.P.